Analysis of Interest in Shopping for Goods Online at Mitha Mum Shop Palu - Abd. Kadir, Haris; Sarifuddin, Sarifuddin; Ma’rifatul, Hasmitha (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This study aims to determine the interest in shopping for goods online at Mitha Mum Shop Palu. The results of the research on the distribution of respondents on the statement of wanting to buy products at Mitha Mum Shop Palu because of the variety of answers to agree as many as 15 people or 16.3% strongly, Agree as many as 59 people or 64.1% and neutral as many as 18 people or 19.6 %. The results of the distribution of respondents to statements referencing Mitha Mum Shop Palu products to others answered strongly agree as many as 22 people or 23.9%, Agree as many as 49 people or 53.3%, neutral as many as 20 people or 21.7% and disagree as many as one people or 1.1%. The results of the distribution of respondents to the question feel happy to buy products at Mitha Mum Shop Palu that respondents who answered strongly agree as many as 18 people or 19.6%, agree as much as 51 or 55.4%, and neutral as many as 23 people or 25%. The results of the distribution of respondents to questions looking for information on the latest products at Mitha Mum Shop Palu that respondents who answered strongly agree were 23 people or 25%, Agree as many as 55 or 59.8% and neutral as many as 14 people or 15.2%.